(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
By locus of control in Social Psychology is meant the source of control in one’s given in every person’s pattern of behaviour falling into external and internal With external control locus, a person who attributes the control locus of behaviour, as originating from outside self. In other words, one’s failure or success is controlled by outside forces and therefore, there is not much that can be done to exercise control of such behaviour. In contrast, a person who has internal locus of control holds the view that she or he is responsible for his/her behaviour, as it does not occur on the basis of luck or chance. . In short, this served as the motivation for wishing to determine the University of Nairobi students’ locus of control among both genders, male and female students.The sample size comprised 127 females and 97 males, giving a total of 224 university students. Their age ranged from 20 to 55 years. The participants were all taking psychology as a major subject.A questionnaire comprising 25 pairs of statements was used. Each statement had two options for participants to respond to as normally provided for in the Rotter’s Locus of Control Scale.Based on Rotter’s Locus of Control Scale, there emerged both external and internal locus of control participants in uneven proportions. A chi-square statistical analysis was employed. Calculation of: x2 test [2df, N224] = 107.6, <p 0.001; which was statistically significant. Thus confirming that, there was a mean significant difference between external internal locus control participants on their performance based on their locus of control. Specifically, externally oriented participants exceeded internally oriented participants. In conclusion,. In general, locus of control is closely related to achievement and success in life. Moreover, people who feel in control of a situation may experience a sense of empowerment. Furthermore, individuals with a high sense of mastery in academic work believe that they can control most aspects of their lives. On the other hand, those who are unable to gain mastery in academic performance or to exert influence over their circumstances may feel a sense of helplessness.